ANALISIS PERUBAHAN SRUKTUR EKONOMI KOTA BANDUNG MELALUI MODEL INPUT OUTPUT - Teti Sofia Yanti; Siti Sunendiari (Jurusan Akuntansi Politeknik Negeri Bandung, 2016)
Abstract: Implementation of the development done in a particular region is basically a series of implementation process of development planning. Development of Bandung as an integral part of regional and national development is basically an integrative process both at the level of planning, implementation and control on an ongoing basis in order to realize the welfare of society. For the purposes of planning and evaluation of the outcomes of development that is comprehensive both national and regional scale, a model for regional development planning approach can implement the model input output analysis. The use of Multiplier Product Matrix (MPM) to the Table Input Output in 2003 and 2008 illustrate economic structure of the city of Bandung has experienced a change. In 2008, the trade sector has grown very conspicuous compared with other sectors. Trade and road transport sector has increased significantly. Thus the development priorities and investment Bandung should be directed at trade and road transport sector, since both sectors can be a driving force and a strong appeal for the growth of other sectors. Keywords: Power Distribution, Degree of Sensitivity, Multiplier Product Matrix, Input-output Analysis